Research to Practice, Research in Practice: Disseminating Results or Supporting Change? - Mary Beth Bingman; Christine Smith (Adult Education Research Conference, 2001)
This roundtable will provide an opportunity to discuss what the National Center for the Study of Adult Learning and Literacy has been doing to connect research and practice and to explore how to facilitate collaborative associations between practitioners and researchers.